Digital Content Design for Promoting Tourism: A Case Study of Pokdarwis Pandeglang's Instagram - Setiawan, Fathur Rahman Awanissa; Wihardi, Doddy; Jati, Rocky Prasetyo (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2026)
In the digital age, social media platforms such as Instagram have become essential tools for promoting tourism, particularly in rural areas with limited resources. This study explores the role of digital content design in enhancing the visibility of local tourism destinations, focusing on a collaboration between students of the Communication Science program at Universitas Budi Luhur and the Pokdarwis (Tourism Awareness Group) in Sumberjaya Village, Pandeglang, Banten. The collaboration aimed to develop a digital content strategy for promoting the village’s tourism potential through Instagram. The study employed a combination of content creation, audience analysis, and training workshops to empower local residents with the skills to manage and create their own digital content. The project demonstrated a significant increase in engagement on the village’s Instagram account, with followers rising by 40% and higher interaction rates across posts. Key content types included promotional posts, behind-the-scenes footage of local cultural events, and a "hidden gems" series showcasing lesser-known attractions. However, the project also faced challenges, including limited access to high-quality editing tools and varying levels of digital literacy among participants. Despite these challenges, the community's enthusiasm and willingness to learn played a crucial role in overcoming obstacles and ensuring the sustainability of the project. The findings highlight the potential of digital content creation and social media in promoting rural tourism and empowering local communities. The success of this collaboration underscores the importance of ongoing digital literacy training and the need for accessible resources to ensure the long-term effectiveness of such initiatives.